2017
DOI: 10.4236/njgc.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation Shielding Properties of Steel and Iron Slags

Abstract: Using steel slag and two types of (soft and hard) iron slags, ten samples were prepared. Different gamma radiation interaction parameters were computed theoretically and measured experimentally at different energies: 60 keV, 136 keV, 662 keV, 1173 keV and 1332 keV in low and medium energy range using narrow transmission geometry. It has been observed that shielding effectiveness of a sample is inversely proportional to Half Value Layer (HVL). The obtained results were compared with Pure Flyash and it was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Lead possesses specific characteristics, e.g. its HVL increases with increase in energy [34]. To assess the shielding ability of a material, HVL is inversely related to the shielding effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Lead possesses specific characteristics, e.g. its HVL increases with increase in energy [34]. To assess the shielding ability of a material, HVL is inversely related to the shielding effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…The half-value layer (HVL) is the thickness of a material that reduces the radiation level by a factor of 2, which can be described by Equation (7). HVL is very important in radiation-related investigations because it predicts the thickness required to achieve any radiation shielding.…”
Section: Theorymentioning
confidence: 99%
“…Hence, investigating the radioactive behaviour and shielding properties of these materials against X-rays and gamma rays is important. Previous studies have examined the behaviour of the attenuation properties of different types of stainless materials at varying photon energies [7][8][9][10][11][12][13][14][15][16]. Low gamma-ray energies have been widely used in practical radiography and medical diagnoses, where the interaction of gamma rays depends on the photon energy and the composition of materials, that is, the atomic numbers of elements.…”
Section: Introductionmentioning
confidence: 99%
“…Kaur et al conducted a literature survey on different metallic alloys classified based on the base metal involved (Ni, Pb, W, Cu, and Fe) as shielding materials for gamma rays. For Fe-based alloys, the results indicated that the steel alloy (Type 304) offers gamma-ray shielding properties better than those of the other Fe-based alloys under the survey [11][12][13][14][15]. Alloys made of iron, chrome, and nickel (Fe/Cr/Ni) in different proportions were investigated as shielding materials for gamma rays by Akman et al The results indicated that Fe/Cr16Ni72 alloy has the best shielding performance against gamma rays, while Fe/Cr17/Ni7 alloy shows the worst performance among the investigated ternary alloys [16].…”
Section: Introductionmentioning
confidence: 99%